RNA-induced intensification of antibacterial resistance and aggravation of infection - Zemskov, V M (Journal of hygiene, epidemiology, microbiology, and immunology, 1977)
The injection of yeast total RNA, transfer RNA or sodium nucleinate into the organism of experimental animals induced the development of non-specific resistance to pathogenic salmonellae, staphylococci and escherichiae 4-6 hours after the administration of the preparations; this resistance persisted during several days. The content of serum lysozyme rose and interferon was induced in the stimulated animals, but the state of resistance was not transferred with serum. It was due to mobile phagocytes the number of which increased considerably and so did their digestive activity. Simultaneous administration of RNA and pathogenic salmonellae and staphylococci was accompanied by aggravation of infection and acceleration of the lethal outcome. The mechanism of this phenomenon consists in the acceleration of proliferation of the microorganisms and in the selection of their virulent clones under the effect of RNA which was demonstrated in experiments in vivo and in vitro. It is believed that endogenous nucleic acids participate in the development of the natural infectious process, in bacterial complications of viral infections and in autoinfection during radiation sickness.
Keywords: RNA; imunita; stafylokokové infekce; Animals; Immunity; Staphylococcal Infections; bakteriální infekce; Streptococcal Infections; Bacterial Infections; Mice; streptokokové infekce; myši; zvířata